THE IMPORTANCE OF ROLE-PLAYING GAMES IN TEACHING A FOREIGN LANGUAGE - Baymirzaeva Feruza Ibraximovna (Web of Journals Publishing, 2025)
This article explores the significance of role-playing by analyzing its key components, including objectives, functions, role content, and the socio-psychological and didactic conditions that shape its implementation. Additionally, it examines the structural connections that ensure the coherence of role-playing in response to various external and internal changes. The role itself is regarded as a fundamental element of the educational and communicative context, reflecting its core parameters.
Keywords: Role-playing, foreign language teaching, communicative skills, educational games, motivation, simulation, fluency, interaction, didactic conditions, communicative competence.